Brain Tumour Diagnosis and Relationships Among Patients: A Social Science Perspective on Changing Tumour Classification. (1st October 2022) - Llewellyn, Henry; Dulley, Louise; Higgs, Paul; Louis, David; Sampson, Elizabeth; Stone, Paddy; Thorne, Louis
Abstract: AIMS: Peer-to-peer relationships between people with a brain tumour are critical to how they cope with illness. These are often premised on shared diagnoses. However, as molecular genetic/epigenetic markers revise tumour classification, the terms of such relationships could also change. We explore these relationships and the potential repercussions for patients whose diagnoses are revised according to new tumour classification. METHOD: We draw on two UK-based ethnographic studies of brain tumour care. The first examined how patients navigated complex healthcare systems (2014-2016); the second explored changing classification and personalised medicine (2020-2021). Both involved repeated qualitative interviews with patients, families, clinicians and classification experts, and observations of routine care. Here, we focus on interviews and observations with patients (N=29). RESULTS: Patients described how peer-to-peer relationships helped them understand their condition, envision their futures, find solidarity, navigate medical decisions, and access non-standard treatments. Many described the importance of finding people who shared their diagnosis. One patient, whose diagnosis was revised to a less aggressive tumour years after being first diagnosed, described how a radical change in prognosis challenged her relationships with peers, and contributed to significant survivor guilt as she outlived them. CONCLUSION: Our findings confirm the importance of peer-to-peer relationships for patients. They suggest how changing tumour classification could have significant unforeseen social and psychological impacts for patients, including survivor guilt, by changing the nature of such relationships. We speculate that this will become more common in an era of personalised medicine and when breakthroughs in cancer understanding are more rapidly integrated in routine care.